STRATEGI PENGEMBANGAN KARIER DAN RETENSI KARYAWAN PADA LEMBAGA KEUANGAN SYARIAH DI KECAMATAN MAJENANG KABUPATEN CILACAP - Yosinta Pangestuti; Supar Supar; Akhman Rohimat; Yanuar Maulana (Institut Agama Islam K.H. Sufyan Tsauri, 2025)
This study examines the career development strategies and factors influencing employee retention at Islamic Financial Institutions (IFIs) in Majenang District, Cilacap Regency. The research's background is the dynamic role of IFIs in the economy and the unique challenge of managing human resources who are not only technically competent but also possess Sharia integrity. Employee retention is a crucial issue as qualified human resources with sharia integrity are often targeted for recruitment by competitors, both other IFIs and conventional institutions. This research used a qualitative approach with a case study method, where data was collected through in-depth interviews with managers, leaders, and employees from BSI KCP Diponegoro Majenang, BPRS Syuriah Majenang, and BMT Surya Utama Majenang. The findings indicate a significant difference in the strategies implemented: BSI uses a formal and structured approach, consistent with the Competency-Based Career Planning Model and the Dual Career Path Model. Meanwhile, local IFIs adopted an informal and personal approach through coaching and discussions, aligning with the concept of informal learning and the Protean Model. The main factors influencing employee retention were spiritual motivation viewing work as an act of worship and a trust (amanah) a supportive work environment, and fair leadership. Employee retention is successfully achieved through the integration of sharia values into human resource management, creating an organizational culture based on ukhuwah (brotherhood) and amanah (trust).